Risk factors associated with a high incidence of sexually transmitted infections in Beitbridge, Zimbabwe - Anelle Siziba; Wilfred N. Nunu; Nicholas Mudonhi; Vuyelwa Ndlovu; Ofhani Munyai; Brighton Ndlovu; Edmond Sanganyado (AOSIS, 2022)
Background: Sexually transmitted infections (STIs) are a major public health challenge, particularly in developing countries where the health infrastructure is often poor. Despite having a number of interventions in Beitbridge (such as the 24-h wellness centre), Zimbabwe, the incidence and prevalence of STIs is increasing. Objectives: This study, therefore, aims to assess the risk factors associated with the high incidence of STIs in urban Beitbridge. Method: A case-control study was conducted on 30 respondents who had suffered from STIs (selected from the registers at Beitbridge hospital and followed up) and 90 respondents who had not suffered from STIs (from the community) who resided in Beitbridge for at least 6 months and this excluded all those who were in transit. The factors contributing to the high incidence of STIs were identified using a pretested interviewer-administered semi-structured questionnaire in conjunction with a Likert scale to establish the attitudes and risk behaviours of the respondents on STIs. Results: A significant association was observed between high STI incidences and the nature of occupation (odds ration [OR]: 3.8), area of residence (OR: 2.78), number of sexual partners (OR: 7.56), payment demanded for sex (OR 22), condom use (OR: 3.7), alcohol use (OR: 2.86), and suspicion that partners had other sexual companions (OR: 15.5). Furthermore, a larger proportion of controls were knowledgeable on STIs as compared to the cases who participated in the study. Conclusion: There is a need to develop awareness strategies that foster safe sexual practices, particularly among populations who do not choose abstinence or a single sexual partner lifestyle.